Nomenclatural and taxonomic notes on Sesleria sect. Argenteae (Poaceae) - Di Pietro, Romeo; Kuzmanović, Nevena; Iamonico, Duilio; Lakušić, Dmitar (Phytotaxa, 2017)
In this paper we typify and discuss 14 species and infraspecies names belonging to Sesleria sect. Argenteae (Poaceae). Lectotypes are designated for the names S. alba, S. anatolica, S. anatolica var. rossica, S. anatolica var. voronovii, S. doerfleri, S. gigantea, S. latifolia, S. latifolia var. serpentinica, S. pontica, S. robusta, S. sillingeri, S. vaginalis and S. wettsteinii. A neotype is designated for the name S. nitida. Previous typifications and holotypes for other names in S. sect. Argenteae are summarized.